Creative Economic Development: Palm Sugar Based on Local Potential as A Datar Village Tourism Support - Intan, Dede; Hendrawan, Budi; Pratiwi, Anggia Suci; Saputra, Jumadil; Brahmantia, Bayu; Saputra, Nadia; Hermawan, Riki; Julieta, Salma; Islah, Tsani; Syntha, Bunga; Mujiarto, Mujiarto (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The purpose of this service program is to make a significant economic contribution and to create a creative and innovative community regarding the packaging of Palm Sugar with the Demonstration method. The partners of this activity are palm sugar makers from RW 06 Serang Village. The problems faced by partners are: 1) there is still a lack of knowledge about the packaging of Palm Sugar. The method of activity is lectures and demonstrations accompanied by questions and answers. The lecture method is needed to explain the packaging of palm sugar, demonstration method to show the working process of palm sugar packaging. while the question and answer session is to give participants the opportunity to overcome the obstacles they may face. The result of this program is an increase in understanding and improvement in the packaging of Palm Sugar. With this service program, understanding and exploring self-potential increases. Starting from identifying ideas as discussion material, then exploring ideas, developing designs, producing, packaging and marketing them. On packaging, i.e. product packaging and trade packaging, through websites or the like.